2023
DOI: 10.1002/inf2.12468
|View full text |Cite
|
Sign up to set email alerts
|

Layer‐controlled nonlinear terahertz valleytronics in two‐dimensional semimetal and semiconductor PtSe2

Minoosh Hemmat,
Sabrine Ayari,
Martin Mičica
et al.

Abstract: Platinum diselenide () is a promising two‐dimensional (2D) material for the terahertz (THz) range as, unlike other transition metal dichalcogenides (TMDs), its bandgap can be uniquely tuned from a semiconductor in the near‐infrared to a semimetal with the number of atomic layers. This gives the material unique THz photonic properties that can be layer‐engineered. Here, we demonstrate that a controlled THz nonlinearity—tuned from monolayer to bulk —can be realized in wafer size polycrystalline through the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The THz E‐field is seven times less for PtSe 2 than for Pt. Considering that the absorption length at the pump laser wavelength (λ = 800 nm) of Pt (respectively PtSe 2 ) is 10 nm [ 51 ] (respectively 5 nm, [ 52,53 ] ) we can deduce θ SHE (Pt)/θ SHE (PtSe 2 ) ≈ 3.5. By spin pumping (see Figure , Supporting Information), we find θ SHE (Pt)/θ SHE (PtSe 2 ) ≈ 9.…”
Section: Resultsmentioning
confidence: 99%
“…The THz E‐field is seven times less for PtSe 2 than for Pt. Considering that the absorption length at the pump laser wavelength (λ = 800 nm) of Pt (respectively PtSe 2 ) is 10 nm [ 51 ] (respectively 5 nm, [ 52,53 ] ) we can deduce θ SHE (Pt)/θ SHE (PtSe 2 ) ≈ 3.5. By spin pumping (see Figure , Supporting Information), we find θ SHE (Pt)/θ SHE (PtSe 2 ) ≈ 9.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, polarized terahertz (THz) emission spectroscopy based on ultrafast femtosecond lasers is a powerful optical tool for generating and detecting ultrafast spin photocurrents 24 , 25 . Very recently, THz emission has been observed in centrosymmetric Dirac semimetal PtSe 2 films due to the photon drag effect 26 , 27 and a second nonlinearity from a structural asymmetry 28 . Remarkably, Luo et al 5 observed the light-induced transient phase transition and hence giant photocurrent (i.e., THz emission) in bulk Dirac semimetal ZrTe 5 .…”
Section: Introductionmentioning
confidence: 99%